La inconsistente Legislación Penal Ecuatoriana, en relación a los delitos del patrimonio cultural del estado - Bautista Gutiérrez, Milton Edgardo (2015)
The cultural patrimony is the valuation of the things that has a symbolic value of diffuse situations, because this cultural patrimony is not exclusive of a person, but of the sector or community where he/she is, but its historical value doesn't have price, but rather he/she has a value characteristic of cultural identification. As for the cultural patrimony, classified as international humanitarian right, it doesn't mean that their protection is in times of war, but rather you happening historical of the humanity, the one that identifies us, symbolizes and we make part of a certain culture, with the purpose of premature the historical roots from where we come. The sanction is the pain for the lack or made fact. As for the crimes to the cultural patrimony of the State, it is necessary to indicate that the integral penal legislation considers them as goods protected to the defined ones as such for the international effective instruments of the International Humanitarian Right, it is hence that the integral penal legislation gives them the human being's special unavoidable protection, as humanitarian patrimony. As for the crimes against the cultural patrimony, the deeper of the crime goes since against the sanctions this crime it is not simple, but the law it considers it that he/she goes in against the international humanitarian right, for what you cannot sanction with hardships of six months to two years, or until five or seven years, but rather to be crimes against this international humanitarian right the sanctions they should be more drastic, to be of for half two elements the penal type that is the cultural patrimony and the fundamental right that it is the humanitarian right. The results that they have arisen in the development of this investigation they should be good to improve the safeguard of the patrimonial Ecuadorian cultural goods, since juridical social considerations of character exist, related with the effective enjoyment of the rights that you/they attend us, to more than the protection and diffusion that it should be given to our cultural genesis. This investigation work contemplates some reformations that have been applied in the international context, but with the particularity that they have been adapted to the Ecuadorian reality